Pemanfaatan Santan Kelapa sebagai Substitusi Susu Sapi pada Pembuatan Roti Bluder - Dela Andriyani; Setyo Widiarto (Eduturisma, 2025)
Bluder bread is a traditional bakery product in the rich dough category known for its very soft texture. The use of cow's milk (fresh milk) as the main liquid ingredient often poses a challenge for consumers with specific diets or lactose intolerance. This study aims to analyze the utilization of coconut milk as a 100% substitution for cow's milk in the production of bluder bread and to determine the level of consumer preference for this innovative product. The research method used is a quantitative experiment with data collection techniques through hedonic tests (preference tests). The panelists in this study consisted of 74 hospitality students at Asa Indonesia University, selected through purposive sampling techniques. The results showed that the substitution of coconut milk produced bluder bread with a finer texture and a stronger savory aroma. Based on data analysis, the experimental sample (coconut milk) obtained a higher mean value than the control recipe across all indicators: color (4.23), aroma (4.46), texture (4.31), and taste (4.50), all of which fell into the "Highly Liked" category. The conclusion of this study is that coconut milk is highly feasible as a substitute for cow's milk because it can enhance the sensory quality and consumer acceptance of bluder bread.